Exosomal lncRNAs and cancer: connecting the missing links - Naderi-Meshkin, Hojjat; Lai, Xin; Amirkhah, Raheleh; Vera, Julio; Rasko, John E. J.; Schmitz, Ulf (Bioinformatics, 2019)
Motivation: Extracellular vesicles (EVs), including exosomes and microvesicles, are potent and clinically valuable tools for early diagnosis, prognosis and potentially the targeted treatment of cancer. The content of EVs is closely related to the type and status of the EV-secreting cell. Circulating exosomes are a source of stable RNAs including mRNAs, microRNAs and long noncoding RNAs (lncRNAs).
CRIS-Team WoS Importer:2019-03-06